ANALISIS KORELASI SIKAP PETANI DENGAN ADOPSI TEKNOLOGI BUDIDAYA CABAI DI SULAWESI SELATAN - Eka Triana Yuniarsih; A. Nixia Tenriawaru; Siti Haerani; Amiruddin Syam (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
Correlation Analysis of Farmers Attitudes on Adoption of Chilli Cultivation Technologies in South Sulawesi. The change in the adoption of technology by farmers from traditional systems to modern systems is one form of changing attitudes and behavior of farmers. The speed and level of utilization of agricultural technology innovation is considered to decrease due to the attitude of farmers who still reject these technological innovations. The existing agricultural extension is tended to given since the technology product is introduced regardless the geographical and economic conditions of farmers. The purpose of this study was to determine the correlation between farmers' attitudes and the adoption of chili cultivation technology in South Sulawesi. This study was conducted from May to July 2017. The study site was in Maros district, Tanralili sub-district, consisting of 3 villages, namely Todopulia, Borong and Lekopancing. The assessment was carried out through observation and interviews using a questionnaire to 85 respondent farmers. The data collected were primary data consisting of demographic information such as age, education level, gender, land area, farming experience; data on farmer attitudes regarding cognitive, affective and conative aspects; adoption of farmers related to chili cultivation technology. Secondary data were taken from related agencies and previous research reports from journals and websites. The data were analyzed descriptively and quantitatively using the Chi Square test of independence. The results showed there was no significant correlation between attitudes from cognitive and affective aspects with the level of adoption of chili cultivation technologies by farmers. However, attitudes from the conative aspect had a significant correlation with the adoption of chili cultivation technology. The correlation between farmer attitudes and the decision to adopt a technology was strongly influenced by internal factors (knowledge and experience) and external factors (land suitability, ease of farming, availability of facilities and infrastructure and support from farmer groups).Keywords: correlation, attitudes, adoption, technology, chilliABSTRAKPerubahan adopsi teknologi oleh petani dari sistem tradisional ke sistem modern merupakan salah satu bentuk perubahan sikap dan perilaku petani. Kecepatan dan tingkat pemanfaatan inovasi teknologi pertanian dinilai menurun karena sikap petani yang masih menolak inovasi teknologi tersebut. Penyuluhan teknologi pertanian saat ini cenderung sudah ditentukan, karena produk teknologinya diintroduksikan tanpa melihat kondisi geografis dan ekonomi petani. Tujuan pengkajian ini untuk mengetahui korelasi sikap petani dengan adopsi teknologi cabai di Sulawesi Selatan. Pengkajian ini dilaksanakan pada bulan Mei sampai Juli tahun 2017. Lokasi pengkajian di Kabupaten Maros, Kecamatan Tanralili, terdiri dari 3 desa yaitu Todopulia, Borong, dan Lekopancing. Pengkajian dilakukan melalui observasi dan wawancara menggunakan kuesioner terhadap 85 orang petani responden. Data yang dikumpulkan adalah data primer terdiri dari informasi demografis seperti usia, tingkat pendidikan, jenis kelamin, luas lahan, pengalaman bertani; data sikap petani menyangkut aspek kognitif, afektif dan konatif; dan adopsi petani terkait teknologi budidaya cabai. Data sekunder diambil dari instansi terkait dan laporan penelitian sebelumnya dari jurnal dan website. Analisis data yang digunakan adalah analisis deskriptif dan analisis kuantitatif menggunakan uji independency Chi Square. Hasil yang diperoleh adalah tidak terdapat korelasi signifikan antara sikap dari aspek kognitif dan afektif dengan tingkat adopsi teknoogi budidaya cabai oleh petani. Akan tetapi, sikap dari aspek konatif mempunyai korelasi signifikan terhadap adopsi teknologi budidaya cabai. Korelasi sikap petani dengan keputusan mengadopsi suatu teknologi sangat dipengaruhi faktor intenal (pengetahuan dan pengalaman) dan faktor eksternal (kesesuaian lahan, kemudahan berusahatani, ketersediaan sarana dan prasarana, dan dukungan kelompok tani).Kata kunci: korelasi, sikap, adopsi, teknologi, cabai